Introduction to Special Issue: Future-oriented Pedagogies in Practice: Innovation and Agency - Mehlsen, David Thystrup; Christensen, Jeppe Kiel; Breum Ramsgaard, Michael (Tidsskrift for Social Innovation & Transformativ Entreprenørskabsdidaktik (SITE), 2026)
Introduction to the special issue that addresses the role of education in these unruly times, and how we can develop future-oriented pedagogies that promote innovation, imagination, action, and hope.